Height‐Latitude Patterns of Interannual Climate Variability in the Upper Mesosphere and Lower Thermosphere During Spring and Autumn Months - Zhang, Liang; Liu, Zhongfang; Tinsley, Brian (Geophysical research letters, 2025)
The upper mesosphere and lower thermosphere (UMLT) remains the least explored and least understood atmospheric region. Using Microwave Limb Sounder and Sounding of the Atmosphere using Broadband Emission Radiometry observations, we demonstrate the interannual variability of UMLT climate during spring and autumn months is controlled by bottom‐up processes: tropical upwelling drives the transport of H2O, increasing atomic hydrogen (H) which destroys O3; the interannual variability of atomic oxygen (O) coincides with that of O3 due to the ozone photochemical equilibrium; radiative and chemical heating of Ox (O and O3) influences temperatures above 90 km (T90). This “upwelling—H2O—Ox—T90” link propagates upward and poleward via dynamic transports. Temperatures at ∼20°S/N near 80 km (T80), dominated by adiabatic cooling, serve as an indicator of tropical upwelling. Notably, mid‐to‐high‐latitude T90 is positively correlated with low‐latitude T80 in both hemispheres, and the interannual variability of H2O, O3, and T90 exhibits remarkable interhemispheric symmetry. These bottom‐up processes may affect solar signal extractions. Plain Language Summary The upper mesosphere and lower thermosphere, a transition region between atmosphere and space, is subject to a variety of forcing. This study reveals that atmospheric dynamics, together with atmospheric chemistry, play an important role on the interannual upper mesosphere and lower thermosphere (UMLT) climate through tropical upwelling‐driven processes during equinox seasons. Consequently, the UMLT climate is highly structured, exhibiting height‐latitude dependent spatial patterns in the interannual variability of variables including H2O, H, O3, O, and Temperature. No matter whether tropical upwelling is significantly or insignificantly correlated with solar 11‐year cycle, the dynamic correlations potentially distort solar correlations with the temperature near 0.001 hPa. Key Points During spring and autumn months, the climate of the upper mesosphere and lower thermosphere is bottom‐up controlled by tropical upwelling Water vapor is transported upward and poleward by tropical upwelling, modulating atomic hydrogen, ozone, atomic oxygen, and temperatures The climate exhibits interhemispheric symmetric height‐latitude patterns, possibly complicating solar signal extraction near 90 km